2008
DOI: 10.12693/aphyspola.113.595
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of Encapsulated Magnetite in PLGA Nanospheres

Abstract: In this study, the biocompatible magnetic fluid was encapsulated in biodegradable polymer PLGA (poly D,L/lactide-co-glycolide acid) by the nanoprecipitation method. We characterized these spheres in terms of morphology, magnetite content and magnetic properties. The results showed good encapsulation with magnetite content 22wt% and magnetization 3.4 mT. The transmission electron microscopy and scanning electron microscopy images showed that magnetic particles have almost a spherical shape with approximate size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 3 publications
3
4
0
Order By: Relevance
“…Two characteristics of FTIR spectra of hydrophilic nanoparticles are interesting to remark. First, we do not observe the presence of 11‐AATS; second, the FTIR spectra are in agreement with the literature for PEG‐ and DEXTRAN‐coated nanoparticles …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Two characteristics of FTIR spectra of hydrophilic nanoparticles are interesting to remark. First, we do not observe the presence of 11‐AATS; second, the FTIR spectra are in agreement with the literature for PEG‐ and DEXTRAN‐coated nanoparticles …”
Section: Resultssupporting
confidence: 90%
“…First, we do not observe the presence of 11-AATS; second, the FTIR spectra are in agreement with the literature for PEG-and DEXTRAN-coated nanoparticles. 38,39 SPA measurements Figure 4 shows the time dependence of the temperature of an aqueous-based ferrofluid containing our SPIONs with concentration of 0.5 wt % in the presence of an ac magnetic field with H 5 13 kA/m and f 5 250 kHz. We observed an increase of $3.2 C and 2.5 C in only 10 s for the DEXTRAN-and PEG-coated SPIONs, respectively.…”
Section: Ftir and Hydrodynamic Radiusmentioning
confidence: 99%
“…As determined by DLS measurements in water (Figure 2A), the average hydrodynamic diameter of these bicompartmental particles decreased to 602±200 nm after calcination. This is consistent with the shrinkage of particles during condensation and thermal treatment 29. Assuming the density of PLGA and titania to be 1.2 and 4 g/cm 3 , respectively, we estimated an average diameter reduction of 25%, which is in good agreement with the results of the TGA analysis.…”
Section: Methodssupporting
confidence: 88%
“…[12, 13, 21, 22] Herein, we demonstrated WBPLP-/BPLP-conjugated MNP structures of the DICT-NPs. Figure 1A shows schematic representation of WBPLP-MNPs and BPLP-MNPs.…”
mentioning
confidence: 99%
“…It was frequently observed that there was a decrease in saturation magnetization when MNPs were coated with various polymers such as polystyrene, [25] PNIPAAm, [12] PLGA, [21] and PEG. [22] The remanence of WBPLP-MNPs and BPLP-MNPs was 5.14 and 5.77 (M r M s −1 ), respectively, as compared to 6.73 (M r M s −1 ) in the case of bare MNPs. Whereas, the coercivity of WBPLP-MNPs and BPLP-MNPs was 50.59 and 59.72 Oe, respectively, as compared to 65.23 Oe in the case of bare MNPs (Supporting Information, Table S2).…”
mentioning
confidence: 99%